Fish Scales and Their Biomimetic Applications - Yaseen, Asim Asghar; Waqar, Taha; Khan, Muhammad Azhar Ali; Asad, Muhammad; Djavanroodi, Faramarz (Frontiers in Materials, 2021)
Biomaterials are evolving quite rapidly over the span of last decade. Many applications have been considered towards their involvement in saving lives in the line of duty for law enforcement agencies and military operations. This article discusses recent work on the role of biomaterials that can be considered as a competitive alternative to composites, being used against ballistic impacts. The fish scaled biomaterials are focused in this paper, highlighting their excellent mechanical properties and structural configurations. In its natural environment, scale provide fishes with an armour plating which is significantly effective in their survival against predator’s attacks and the impacts inflicted from sharp teeth. These bio-inspired materials, if engineered properly, can provide an excellent alternative to current Kevlar® type armours, which are significantly heavier and can cause fatigue to human body over long-term usage. The investigated materials can provide effective alternatives to heavier and expensive materials currently used in different industrial applications. Additionally, some recent development in the usage of fish scales as a biomaterial and its applications in rapid prototyping techniques are presented. Finally, this review provides useful information to researchers in developing and processing cost-effective biomaterials.